The International and Political Journal: Algeria's management of multilingualism and cultural diversity: The impact of the constitutionalizing of the Amazigh language alongside the Arabic language in the new constitution on social peace - Rashak , Assistant lecturer Masara Ali (The International and Political Journal, 2024)
The amazigh language become an official language, after the arabian language in Our country. It includes within the educational programs, then the amazigh language considers as an important politics to confirm its existence and to Complete the national identity, this policy has many and different goals.We will concentrate on the cultural goal and its rule to complete the national identity from another side.